2006
DOI: 10.1038/sj.bjc.6603487
|View full text |Cite
|
Sign up to set email alerts
|

The role of the VEGF-C/VEGFR-3 axis in cancer progression

Abstract: Vascular endothelial growth factor (VEGF) receptor 3 (VEGFR-3) (also called VEGFR-3) is activated by its specific ligand, VEGF-C, which promotes cancer progression. The VEGF-C/VEGFR-3 axis is expressed not only by lymphatic endothelial cells but also by a variety of human tumour cells. Activation of the VEGF-C/VEGFR-3 axis in lymphatic endothelial cells can facilitate metastasis by increasing the formation of lymphatic vessels (lymphangiogenesis) within and around tumours. The VEGF-C/VEGFR-3 axis plays a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
186
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(203 citation statements)
references
References 49 publications
5
186
0
12
Order By: Relevance
“…However, in this study, basal VEGF immunoreactivity was lower in tumors from apigenin-treated animals. Since VEGF has been shown to be involved in survival and proliferation of mammary tumor cells [39,40,45,46], it is possible that loss of the angiogenic growth factor leads to tumor cell loss. Furthermore, although blood vessel density was similar in tumors from all animal groups, apigenin-treatment correlated with smaller blood vessel lumen size.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, basal VEGF immunoreactivity was lower in tumors from apigenin-treated animals. Since VEGF has been shown to be involved in survival and proliferation of mammary tumor cells [39,40,45,46], it is possible that loss of the angiogenic growth factor leads to tumor cell loss. Furthermore, although blood vessel density was similar in tumors from all animal groups, apigenin-treatment correlated with smaller blood vessel lumen size.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-C is a member of the VEGF family, which regulates lymphatic system formation under physiological and pathological conditions via its specific receptor, VEGFR-3 (26). Since VEGF-C is a specific lymphangiogenic factor, its expression is upregulated in various human malignancies and is typically associated with lymphatic metastasis and poor prognosis (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly expressed in lymphatic endothelial cells, but also in neovascular endothelial cells of the liver, splenic sinusoid, trauma repair tissues and tumor tissues. Studies showed that cancer cells express VEGFR-3/Flt-4, which contributes to malignant tumor progression in various ways (1). In this study, an immunohistochemical streptavidin-peroxidase (SP) method was used to detect the expression of VEGF-C, VEGF-D and VEGFR-3/ Flt-4 in early-stage cervical cancer tissues.…”
Section: Introductionmentioning
confidence: 99%